2007
DOI: 10.1242/dev.02790
|View full text |Cite
|
Sign up to set email alerts
|

The P-type ATPase CATP-1 is a novel regulator ofC. elegansdevelopmental timing that acts independently of its predicted pump function

Abstract: During postembryonic stages, metazoans synchronize the development of a large number of cells, tissues and organs by mechanisms that remain largely unknown. In Caenorhabditis elegans larvae, an invariant cell lineage is tightly coordinated with four successive molts, thus defining a genetically tractable system to analyze the mechanisms underlying developmental synchronization. Illegitimate activation of nicotinic acetylcholine receptors (nAChRs) by the nicotinic agonist dimethylphenylpiperazinium (DMPP) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 72 publications
3
26
1
Order By: Relevance
“…They are involved in morphogenesis and oncogenesis, and these functions are independent of their transport activity (49 -51). In Caenorhabditis elegans, the cation-transporting ATPase CATP-1 interacts with the insulin/IGF and Ras-MAPK pathways to control several postembryonic events, independently of its transport function (52). A potential extracellular ligand has not been identified in this case.…”
Section: Discussionmentioning
confidence: 98%
“…They are involved in morphogenesis and oncogenesis, and these functions are independent of their transport activity (49 -51). In Caenorhabditis elegans, the cation-transporting ATPase CATP-1 interacts with the insulin/IGF and Ras-MAPK pathways to control several postembryonic events, independently of its transport function (52). A potential extracellular ligand has not been identified in this case.…”
Section: Discussionmentioning
confidence: 98%
“…The C. elegans genome encodes five Na + /K + ATPase α subunits, EAT-6, C01G12.8, C09H5.2, C02E7.1 and CATP-1 (Okamura et al, 2003;Ruaud and Bessereau, 2007). catp-1 is expressed in the epidermal cells and the excretory duct cell (Ruaud and Bessereau, 2007). Using GFP fusion constructs, we found that C01G12.8 was expressed in the germline, C09H5.2 in hypodermal cells, and C02E7.1 undetected in any tissues.…”
Section: Postsynaptic Na + /K + Atpase Confers Hypersensitivity To Acmentioning
confidence: 93%
“…To clarify the tissue-specific expression profile of eat-6, we also examined the expression patterns of other Na + /K + ATPase α subunits in the C. elegans genome. The C. elegans genome encodes five Na + /K + ATPase α subunits, EAT-6, C01G12.8, C09H5.2, C02E7.1 and CATP-1 (Okamura et al, 2003;Ruaud and Bessereau, 2007). catp-1 is expressed in the epidermal cells and the excretory duct cell (Ruaud and Bessereau, 2007).…”
Section: Postsynaptic Na + /K + Atpase Confers Hypersensitivity To Acmentioning
confidence: 99%
See 1 more Smart Citation
“…15) in the germ line of C. elegans 16,17 .This technique has been used successfully in forward genetic screens to identify genes of interest [18][19][20][21] . This system has three main advantages.…”
Section: Introductionmentioning
confidence: 99%